2016
DOI: 10.15408/etk.v15i2.3331
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ASEAN-China Free Trade Area (ACFTA) on Indonesia Export

Abstract: ASEAN-China Free Trade Area (ACFTA) is an agreement between the members of ASEAN and China to create a free trade area by removing tariff and non-tariff barriers. This agreement begins with the signing of the agreement on November 5, 2002 in Phnom Penh. Implementation is done in phases beginning January 1, 2004. The purpose of this study determines the effect of the implementation of ACFTA on Indonesia's exports to the ASEAN countries and China. This study complements previous research regarding the ACFTA. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Therefore, it is expected that the government should always think of the interests of its country from both the upper (bourgeois) and the lower (proletarian) layers before receiving any form of aid from abroad. Because this problem requires the role of the government to face and respond to the emergence of competition in free market trade especially to micro and medium-sized enterprises (SMEs) that are located in regional areas or areas that are not accessible by the government both in terms of security and economy (Hardiani, 2017) The…”
Section: Impact Of Acfta For Msmes In Indonesiamentioning
confidence: 99%
“…Therefore, it is expected that the government should always think of the interests of its country from both the upper (bourgeois) and the lower (proletarian) layers before receiving any form of aid from abroad. Because this problem requires the role of the government to face and respond to the emergence of competition in free market trade especially to micro and medium-sized enterprises (SMEs) that are located in regional areas or areas that are not accessible by the government both in terms of security and economy (Hardiani, 2017) The…”
Section: Impact Of Acfta For Msmes In Indonesiamentioning
confidence: 99%
“…In the case of the combined group of dairy products, the trade creation effect is predominant on the imports, but it is surpassed by the trade diversion effect in terms of exports. On the other perspectives, by focusing on individual countries, [5] found that ACFTA holds a substantial positive impact on Indonesia's exports to the ASEAN countries and China. In line with the trade liberalization, where the ACFTA is one form of trade liberalization, reducing and eliminating tariffs will enhance the export flows.…”
Section: Past Studies On Acfta and Trade Effectsmentioning
confidence: 99%
“…The impact of ACFTA on Indonesian export itself has been studied by several studies, and it is found that the ASEAN -China Free Trade Agreement stimulate export from Indonesia (Ibrahim, Permata dan Wibowo, 2010;Sheng, Tang dan Xu, 2014;Yang dan Martínez Zarzoso, 2014;Indriyani, 2016). Also, the tariff liberalization under the ASEAN -India Comprehensive Cooperation Agreement (CECA) has given a benefit to ASEAN countries since India's tariff is relatively higher than ASEAN economies (Yean dan Jia Yi, 2018).…”
Section: Gravity Modelmentioning
confidence: 99%